"Dry bite" in venomous snakes: A review. (July 2017) - Naik, B. Sadananda
Abstract: It is quite interesting that when a venomous snake bites a person and the victim does not suffer from any signs or symptoms of envenomation. A good percentage of venomous snake bites in humans do occur without venom injection. This phenomenon is termed as "Dry" bite in clinical medicine. Though this was not very uncommon in toxicological practice but, our awareness of this problem has increased. In this article an effort has been made to provide an insight into the incidence, pathophysiology and patho-mechanics of this unique medical enigma. Highlights: "Dry bite" is a definitive clinical entity in venomous snake bites. Incidence varies with species of venomous snakes, geographical area. Possible explanations discussed in this review article.